Early-Life Insults Impair Parvalbumin Interneurons via Oxidative Stress: Reversal by N-Acetylcysteine - Cabungcal, Jan-Harry; Steullet, Pascal; Kraftsik, Rudolf; Cuenod, Michel; Do, Kim Q. (Biological psychiatry (1969), 2013)
A hallmark of the pathophysiology of schizophrenia is a dysfunction of parvalbumin-expressing fast-spiking interneurons, which are essential for the coordination of neuronal synchrony during sensory and cognitive processing. Oxidative stress as observed in schizophrenia affects parvalbumin interneurons. However, it is unknown whether the deleterious effect of oxidative stress is particularly prevalent during specific developmental time windows. We used mice with impaired synthesis of glutathione (Gclm knockout [KO] mice) to investigate the effect of redox dysregulation and additional insults applied at various periods of postnatal development on maturation and long-term integrity of parvalbumin interneurons in the anterior cingulate cortex. A redox dysregulation, as in Gclm KO mice, renders parvalbumin interneurons but not calbindin or calretinin interneurons vulnerable and prone to exhibit oxidative stress. A glutathione deficit delays maturation of parvalbumin interneurons, including their perineuronal net. Moreover, an additional oxidative challenge in preweaning or pubertal but not in young adult Gclm KO mice reduces the number of parvalbumin-immunoreactive interneurons. This effect persists into adulthood and can be prevented with the antioxidant N-acetylcysteine. In Gclm KO mice, early-life insults inducing oxidative stress are detrimental to immature parvalbumin interneurons and have long-term consequences. In analogy, individuals carrying genetic risks to redox dysregulation would be potentially vulnerable to early-life environmental insults, during the maturation of parvalbumin interneurons. Our data support the need to develop novel therapeutic approaches based on antioxidant and redox regulator compounds such as N-acetylcysteine, which could be used preventively in young at-risk subjects.